2020
DOI: 10.21101/cejph.a6183
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders and working risk factors

Abstract: Objectives: The authors evaluate situation in the field of musculoskeletal disorders (MSDs) and working risk factors in the Czech Republic. Methods: Analysis of selected data from the Czech National Registry of Occupational Diseases during 2008-2018, description of criteria for recognition of occupational MSDs and risk factors associated with MSDs. Results: 6,152 cases of 6 selected recognized occupational musculoskeletal diseases represent 47% of all recognized occupational diseases. The main proportion forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 2 publications
0
12
1
2
Order By: Relevance
“…Although the literature has shown that working hours and corresponding higher stress levels can promote the development of MSD [32,33], dentists still show a lower prevalence of MSD in all queried regions and time periods, even though they have longer working hours and higher stress levels than the dental assistants in the current study.…”
Section: Discussioncontrasting
confidence: 61%
“…Although the literature has shown that working hours and corresponding higher stress levels can promote the development of MSD [32,33], dentists still show a lower prevalence of MSD in all queried regions and time periods, even though they have longer working hours and higher stress levels than the dental assistants in the current study.…”
Section: Discussioncontrasting
confidence: 61%
“…Musculoskeletal disorders (MSDs) are common skeletal injuries to muscles, bones, nerves, and other systems due to non-compliant working conditions; common skeletal injuries include lower back pain, cervical and shoulder wrist syndrome, and carpal tunnel syndrome [ 3 , 4 ]. MSDs are very common occupational diseases in many industrialized countries, and they constitute one of the biggest occupational health burdens for modern occupational groups [ 5 , 6 ]. As a common group of occupational diseases, MSDs have become the main cause of absenteeism and early retirement among the occupational population, as well as being a major risk factor for occupational disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSD is a term that groups together diseases that affect different parts of the locomotor system caused by its excessive use [ 17 ], caused by prolonged and tiring work and postures, improper unbalanced angles, load handling and repetitive movements [ 18 ]. DUE are accumulated lesions that frequently occur in connective soft tissues, particularly to tendons and their sheaths.…”
Section: Introductionmentioning
confidence: 99%